Simulation of wave refraction in the western waters of Aceh, Indonesia. (December 2018) - Haditiar, Y; Zulfandi, Z; Iskandar, T; Setiawan, I; Sugianto, S; Rizal, S
Abstract: A two-dimensional numerical model which is the solution of a shallow water equation without advection is used for long wave refraction simulations in the western waters of Aceh. The model is discretized with the resolutions of Δx = Δy = 925 meters and Δt = 10 seconds. The bathymetry data used is obtained from SRTM30. As an external force, we use amplitude of 0.3 m and a period of 1 hour. The numerical simulation results are discussed every quarter of the period (T/4, T/2, 3T/4, and T). The comparison between the two scenarios is that the gradient of the sea level with the period of one hour is greater than that of two hours, especially at T/2 and T. For the model with one hour period, when T/2 and T, the currents and gradients converge to Sikandang village in the west coast. While for the model with two hour period, when T / 2 and T currents and gradient of sea level experience a little convergence. According to the theory, the cape and bay form a convergent and divergent zone, respectively. This study confirms this theory.